PHYSIOLOGICAL RESPONSE OF THE EYE YELLOW-STRIPED SCAD (Selaroides leptolepis) AND SHORT MACKEREL (Rastreliger brachysoma) TO THE COLOR OF LIGHT (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
The physiological response of the eye yellow-striped scad (Selaroides leptolepis) and short mackerel (Rastreliger brachysoma) are different for each color of light. The physiological response of the eye fish can be used as an indicator to determine the level of attraction of fish to specific colors of light. This study aims to identify the level of attraction of yellow-striped scad and short mackerel to light white, yellow, green and blue. The research was performed by experiment on lift net. Ten individual yellow-striped scad and short mackerel caged with a net. The fish lighted for 30 minutes. Then the fish was taken the eye, and histological analysis carried out. Data analysis used in this research were regression of fish size, con cells index and speed of con cells movement. The results showed that yellow-striped scad was very responsive to green and blue light. The short mackerel was more responsive to blue light. The average con cells index of yellow-striped scad for blue and green light were 77.3±7.4% and 70.7±6.8%, respectively. On the other hand, the average con cells index of short mackerel for blue light was 79.9±2.0%. The average speed of con cells movement of yellow-striped scad for blue light was 0.0180±0.0028 μm/sec, and the short mackerel for green light was 0.0157±0.0018 μm/sec. Based on the result of study can be conclouded that the yellow-striped scad was very attracted in green and blue light, while short mackerel was very attracted to blue light.